2022
DOI: 10.3389/fimmu.2022.1075916
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B functional cure and immune response

Abstract: Hepatitis B virus (HBV) is a hepatotropic virus, which damage to hepatocytes is not direct, but through the immune system. HBV specific CD4+ T cells can induce HBV specific B cells and CD8+ T cells. HBV specific B cells produce antibodies to control HBV infection, while HBV specific CD8+ T cells destroy infected hepatocytes. One of the reasons for the chronicity of HBV infection is that it cannot effectively activate adoptive immunity and the function of virus specific immune cells is exhausted. Among them, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 148 publications
0
12
0
Order By: Relevance
“…Several studies have demonstrated that baseline quantitative HBsAg < 1,500 IU/ml can effectively predict HBsAg loss after a finite course of IFN-based therapy ( 27 , 28 ). However, HBsAg alone as a predictor could not fully predict the efficacy ( 15 , 29 ) nor reflect the liver’s immune status ( 30 ). Cytokines in serum can indirectly reflect intrahepatic immune response and inflammation ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that baseline quantitative HBsAg < 1,500 IU/ml can effectively predict HBsAg loss after a finite course of IFN-based therapy ( 27 , 28 ). However, HBsAg alone as a predictor could not fully predict the efficacy ( 15 , 29 ) nor reflect the liver’s immune status ( 30 ). Cytokines in serum can indirectly reflect intrahepatic immune response and inflammation ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In CHB, Th1/Th2 and Th17/Treg were in immune imbalance ( 30 , 38 , 39 ), and antiviral treatment partially restored immune cell function ( 30 ). IL2 (Th1 cytokine) activated CD8+T cells and NK cells and promoted their proliferation and cytosolic activity ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mice treated with control siRNA (that therefore maintained high levels of HBV antigenemia) followed by therapeutic vaccination did not all cleared HBV antigenemia despite strong induction of CD4 Tfh and TCR clonal expansions. Given that the main difference with the group that cleared HBV was a more modest plasma cell clonal expansion, it suggests that mounting a CD4 Tfh response alone is not sufficient for clearing HBV and that induction of B-cells is a key factor (33).…”
Section: Discussionmentioning
confidence: 99%
“…Granulocytes, dendritic cells (DCs), macrophages, mast cells, and natural killer (NK) cells play crucial roles as effector cells in various biological processes. The initiation of an effective innate immune response typically occurs when pathogen-associated molecular pattern (PAMP) molecules interact with pattern recognition receptors (PRRs)[ 24 , 25 ]. This interaction triggers the production of chemokines and pro-inflammatory cytokines and the activation of innate immune cells.…”
Section: Possible Immunological Mechanisms Of Hbv Reactivationmentioning
confidence: 99%
“…It is of utmost significance that the implementation of efficient anti-viral medication has the potential to impede the advancement of liver fibrosis and Cirrhosis, offering a pivotal means of managing individuals who are susceptible to severe liver disease resulting from HBV reactivation[ 115 , 116 ]. In addition to their anti-viral properties, the immunomodulatory capacities of NAs, as revealed by Zheng et al [ 25 ], are involved in regulating immunological reactions during the reactivation of HBV. Nucleic acid-based therapies have been observed to lower viral load, reducing viral antigen exposure effectively.…”
Section: Management Strategies For Hbv Reactivationmentioning
confidence: 99%